PENGARUH SOLVABILITAS, UKURAN PERUSAHAAN, OPINI AUDIT DAN UKURAN KAP TERHADAP AUDIT REPORT LAG (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2011-2013) - Lestari, Alit Sri; Ritonga, Kirmizi; Anggraini, Lila (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to examine the influence of solvency, company size, audit opinion and size of public accounting firmto audit report lag.The variabels which used in this study are solvency, companysize,auditopinion,and size of public accounting firm.The sample used in this study are manufacturing companies listed on Indonesia Stock Exchange (BEI)during 2011-2013 period. Companies that a sample of this is the company that contains the information that it contains information that covers all operational definition of research, namely: The company has total assets of 500 billion dollars or more over the 2011-2013 data (financial report) are available published. Data were analyzed with multipleregression method using Statistical Product and Service Solution (SPSS) version 17.0. The result showed that Solvency has significance level 0.027 (p < 0.05), indicating H1 is accepted that solvency influences audit report lag. company size has significance level 0.610 (p>0.05), indicating H2 is unacceptable, so that company size doesn’t influence audit report lag. Audit opinion has significance level 0,000 (p<0,05), indicating H3 is accepted that audit opinion influences audit report lag. Size of public accounting firm has significance level 0,032 (p<0,05), indicating H4 is accepted that size of public accounting firm influences audit report lag.Keywords: Solvency , Opinion, and Report Lag